LncRNA SNHG7 Mediates the Chemoresistance and Stemness of Breast Cancer by Sponging miR-34a - Li, Zhi-hua; Yu, Ni-si; Deng, Qing; Zhang, Yulu; Hu, Yang-yang; Liu, Gang; Huang, Kedi (Frontiers in Oncology, 2020)
Chemoresistance is considered to be an major cause of the recurrence and metastasis of breast cancer (BC). LncRNA SNHG7 has been reported to be upregulated in breast cancer and to promote tumor progression and metastasis. Nevertheless, the function and potential regulatory mechanism of SNHG7 in BC drug resistance are still largely unclear. This study indicated that SNHG7 was highly expressed in chemoresistant BC tissues and cells. . Upregulated SNHG7 might predict a low pCR rate and poor clinical outcome in BC patients.. Knockdown of SNHG7 enhanced drug sensitivity and drug-induced apoptosis in chemoresistant BC cells. In terms of the mechanism, miR-34a was found to be a target of SNHG7 and its expression in breast cancer tissues and chemoresistant cell lines was negatively correlated with SNHG7 expression. Importantly, sh-SNHG7 upregulated miR-34a expression, reduced the percentages of CD44+/CD24−cells, and inhibited sphere-formation and stem cell factor (Oct4, Nanog, SOX2) expression. Functional loss experiments showed that the repressive effect of SNHG7 knockdown on BC cell stemness was partially reversed by transfection with miR-34a inhibitors. In summary, this study indicated that SNHG7 contributed to the chemoresistance of BC and mediated chemoresistance and cancer stemness by sponging miR‐34a.